Creative Thinking and Process Science Skill: Self-Organized Learning Environment on Watershed Conservation Material - Rizal, S.; Putra, A. K.; Suharto, Y.; Wirahayu, Y. A. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
Learning geography plays a role in developing creative thinking and science process skills in students. Creative thinking and process science skills can be used in developing new methods and solutions to solve problems in geosphere phenomena using innovative perspectives. This study uses a quasi-experimental type with a Posttest Only Design. In this study, a purposive sample method was applied with two groups: the experimental group from science class 1 using SOLE and the control group from science class 3 using conventional methods. The instrument uses an essay test to measure the level of creative thinking ability and an observation sheet to measure the level of science process skills. The data analysis used was the Independent-Sample T Test and the Mann-Whitney U test with a significance level of 0.05. The SOLE model significantly affects watershed conservation materials' creative thinking and science process skills. The significance value of the Independent-Sample T-Test of creative thinking skills was 0.001 0.05, and the significance value of the Mann-Whitney U Test of science process skills was 0.000 0.05. The internet's investigative process provides information and mindset in scientific concepts in predicting damage/problems and watershed conservation efforts. In addition, the internet investigation process helps students obtain various literacy and information.